Autonomous teams as a way to increase the engagement of nonprofit members (case study) = Autonomiczne zespoły jako sposób na zwiększenie zaangażowania członków organizacji non-profit (studium przypadku) - Stankiewicz, Janina; Łychmus, Patrycja; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
In the literature on management, engagement is generally discussed in the context of cooperation with paid employees. This article focuses on the rarely analyzed issue - developing the engagement of nonprofit members. Research was carried out on this subject in the association in Zielona Góra, where deficits were found in that area.
Keywords: organizacje non profit; stowarzyszenia; zaangażowanie; non profit organizations; associations; engagement